Strength of Laterite Mixed with GeoPolySoilS for Slope Cover and Protection - Mohamed Jais, Ismacahyadi Bagus; Ahmad Rahaizad, Anis Syahzani; Che Lat, Diana; Md Ali, Mohamed Azizi (International Journal of Sustainable Construction Engineering and Technology, 2023)
Slope stabilization or slope protection is the actions constructed on the slope or nearby areas to keep the slope safe from moving water, erosion, or the negative impacts of sudden outflow. There are a few slope stabilization methods such as geometric method, hydrological method and chemical and mechanical method that can be used to enhance the engineering properties of laterite soil. Among these methods, the chemical method was proven to be a method that is efficient to enhance the geotechnical properties of laterite soil. In this study, GeoPolySoilS was used to mixed with laterite soil to increase the strength of the soil. This study is carried out to investigate the strength of the laterite mixed with GeoPolySoilS for slope cover and protection. For the physical and mechanical properties test, laboratory experiments were conducted on natural laterite soil to determine the natural moisture content, particle size distribution, liquid limit, plastic limit, maximum dry density, optimum moisture content and unconfined compressive strength of the soil. The amount of GeoPolySoilS applied to the laterite soil sample are 0%, 5%, 8%, 10%, 12%, 15%, 18% and 20%. The results of laboratory tests show that by adding an appropriate amount of GeoPolySoilS to the soil, the stability of the slope surface increases, thus able to avoid landslides.